2010
DOI: 10.4995/wrs.2008.632
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the complete replacement of barley and soybean meal with hard wheat by-products on diet digestibility, growth and slaughter traits of a local Algerian rabbit population.

Abstract: Eighty one rabbits were used to study the utilisation of hard wheat by-products on the growth of rabbits from a local Algerian population. At weaning (28 d, 501±99 g), the animals were individually caged and received ad libitum one of the three experimental diets for 49 d. The control diet included 26% wheat bran (W26: control diet), alfalfa, barley and soybean meal. The two other diets were formulated by substituting barley and soybean meal with hard wheat by-products, and contained 60% (W60) or 67% (W67) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
6
6
1
1
Order By: Relevance
“…In certain studies the level was slightly higher; for example, in a study by Lakabi-Ioualitene et al (2008), it ranged from 71 to 76%; in a study by Strychalski, Juśkiewicz et al (2014), from 78 to 83%; while in a study by Gugołek et al (2015), from 80 to 84%. A slightly lower level of digestibility was noted by Volek and Marounek (2009) -from 66 to 69%, and by Volek et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain studies the level was slightly higher; for example, in a study by Lakabi-Ioualitene et al (2008), it ranged from 71 to 76%; in a study by Strychalski, Juśkiewicz et al (2014), from 78 to 83%; while in a study by Gugołek et al (2015), from 80 to 84%. A slightly lower level of digestibility was noted by Volek and Marounek (2009) -from 66 to 69%, and by Volek et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…For testing, typical meat breeds or synthetic lines are most often used. Local breeds with a lower growth rate are used less frequently (AbdelGhany et al 2000;Bielański et al 2008;Lakabi-Ioualitene et al 2008;Kowalska & Bielański 2011;Lounaouci-Ouyed et al 2014;Paci et al 2014). These breeds are most often used in experiments on the extensive breeding and feeding systems.…”
Section: Introductionmentioning
confidence: 99%
“…The review of Lebas (2004) and previous works (Berchiche et al, 2000;Lakabi et al, 2008;Lounaouci et al, 2011b) from our laboratory have demonstrated that this fibrous by-product can be used up to 40-50%. The study of Lounaouci et al (2012) also showed that the incorporation of hard wheat bran up to a rate of 45%, in a growing rabbit's diet without soybean meal, did not impair growth and slaughter performances.…”
Section: Introductionmentioning
confidence: 99%
“…protéines n'affecte pas la croissance, mais peut favoriser l'apparition de diarrhée, ce qui n'a pas été le cas dans cet essai. Les indices de consommation enregistrés sont en deçà des normes dans les deux lots même si celui enregistré dans le lot témoin est conforme à ce que l'on a l'habitude de trouver dans les mêmes conditions [1,13,15]. Cependant, l'aliment RS est le moins efficacement transformé [17].…”
Section: Croissance Et Consommation Alimentaireunclassified